Antimicrobial coatings effectively inactivate multidrug-resistant Candidozyma auris on surfaces - Poelzl, Sabine; Zarschenas, Eva; Nokhbehzaeim, Rozita; Spettel, Kathrin; Kittinger, Clemens (Frontiers in Microbiology, 2025)
Candidozyma auris—formerly known as Candida auris—is an emerging multidrug-resistant fungus causing life-threatening outbreaks, particularly in healthcare settings. Its ability to contaminate hospital equipment, persist on certain surfaces and develop resistance to commonly used antifungal agents makes it a critical priority pathogen. While classical hygiene measures are essential, increasing resistance to disinfectants calls for alternative approaches. One promising strategy is the use of antimicrobial materials on frequently touched surfaces to minimize the survival rate of problematic microorganisms. As literature does not provide a lot of data regarding the survival of Candida genera on surfaces, the present study was undertaken to analyze the survival/elimination of C. auris on different common and specific surfaces. ISO 22196:2011 was used to generate an overview of the efficacy of these surfaces against DSMZ strains of C. auris and C. albicans, respectively. The findings indicate that C. albicans can be regarded as suitable model organism for C. auris. Three clinical C. auris isolates with different genetic characteristics and/or phylogeographic origins yielded similar results to the DSMZ strains, providing a clear indication of the antifungal efficacy of surfaces tested. While reference materials without antimicrobial additives showed no efficacy, a combination of zinc and copper achieved the required 3 log10 reduction after 24 h. Most effective against all fungal strains in two different types of tests was a layer of antimicrobial lacquer, which showed a significant decrease in fungal survival within 1 h. Thus, these surface modifications can be considered as effective tools for fighting C. auris in hygienically critical areas.